2016
DOI: 10.1016/j.reprotox.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Developmental cigarette smoke exposure II: Hepatic proteome profiles in 6 month old adult offspring

Abstract: Utilizing a mouse model of ‘active’ developmental cigarette smoke exposure (CSE) [gestational day (GD) 1 through postnatal day (PD) 21] characterized by offspring low birth weight, the impact of developmental CSE on liver proteome profiles of adult offspring at 6 months of age was determined. Liver tissue was collected from Sham- and CSE-offspring for 2D-SDS-PAGE based proteome analysis with Partial Least Squares-Discriminant Analysis (PLS-DA). A similar study conducted at the cessation of exposure to cigarett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…When paired to the finding of reduced serum glucose levels in the parallel study on liver tissue-specific toxicity in these same animals [47], these findings likely indicate systemic aberrant responses to insulin signaling or possible hyperinsulinemia. Insulin expression and signaling were not assessed within the current study.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…When paired to the finding of reduced serum glucose levels in the parallel study on liver tissue-specific toxicity in these same animals [47], these findings likely indicate systemic aberrant responses to insulin signaling or possible hyperinsulinemia. Insulin expression and signaling were not assessed within the current study.…”
Section: Resultsmentioning
confidence: 88%
“…Aldolase B and Glyceraldehyde-3-dehydrogenase are also part of the glycolytic pathway. The decrease in abundance of these enzymes in the kidney of mature offspring who were developmentally exposed to cigarette smoke, coupled to the approximate 20% reduction in serum glucose levels in these animals [47] and the trend toward a reduction in tissue-specific PEPCK expression, indicates a deficit in glucose availability that may contribute to the decrements in growth and weight that are evident from birth and continue to maturity. It also appears that galactose utilization to produce glucose may be stimulated in the kidney of mature offspring developmentally exposed to cigarette smoke since galactose kinase abundance was increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed descriptions of the experimental methodology can be found within the lead manuscript ([55], liver proteome profiles) for the present series of reports of sustained toxicity of developmental exposure to cigarette smoke. An abbreviated methodology section follows.…”
Section: Methodsmentioning
confidence: 99%
“…These changes included suppression of glycolysis, oxidative phosphorylation, and fatty acid metabolism [52]. In proteome analyses conducted in parallel with our neurobehavioral phenotyping studies, juvenile CSE offspring (aged PD21) from litters identical to those used in the neurobehavioral studies demonstrated altered liver and kidney proteome profiles [53, 54] with sustained impact into adulthood approximately 5 months after cessation of exposure [55, 56]. The current study reports attendant alterations in the hippocampus biomolecular phenotype in these offspring – i.e.…”
Section: Introductionmentioning
confidence: 99%